The influence of different substrate types on the diversity of macrofouling organisms at the submerged coastal ecosystem of Karimunjawa Islands, Indonesia - SAPTO PURNOMO PUTRO; MUHAMAD DAFIQ AL HAQI; FUAD MUHAMMAD; RICHE HARIYATI; M. HELMI (Society for Indonesian Biodiversity, 2024)
Abstract. Putro SP, Haqi MDA, Muhammad F, Hariyati R, Helmi M. 2024. The influence of different substrate types on the diversity of macrofouling organisms at the submerged coastal ecosystem of Karimunjawa Islands, Indonesia. Biodiversitas 25: 3394-3400. Colonizing fouling organisms exhibit taxonomic diversity and distribution in response to environmental variability of the submerged marine ecosystem. This study compares macrofouling organisms found on various substrate types at Menjangan Besar Island, Karimunjawa, Central Java, Indonesia which were varied from coarse to smooth surfaces in the water column. The consisted of High-Density Polyethylene (HDPE) cage framework (3 stations) and lower part of a wooden ship hull are the smooth ones (3 stations), and concrete block at the Menjangan Besar Island dock is the coarse ones (3 stations). Sampling of macrofouling organisms was collected from the substrate within 0.25 m2 area at each station with the purposive random sampling method. Identification of macrofouling organisms was done under Canon MZ25 stereomicroscope. We identified 15 species from 7 classes from Menjangan Besar Island. The most dominant species on concrete blocks was Septifer sp. (96 ind.m-2), on the ship’s hull was Littoraria sp. (416 ind.m-2), and on the cage framework was Crassostrea angulata Thunberg 1793 (240 ind.m-2). The diversity index (H’) of fouling organisms ranged from 0.69 to 1.82, while the evenness index (e) ranged from 0.25 to 0.67, and the dominance index (C) ranged from 0.24 to 0.51. Differences in index values are likely due to factors related to food source distribution and substrate types. Salinity, temperature, and turbidity were the physical-chemical water parameters significantly affecting fouling organism distribution (BIO-ENV, Primer 6.1.5; Corr. value (r)=0.722). Anthropogenic activities such as aquaculture, fishing and tourism in the area are suspected to influence hydrodynamic changes, subsequently affecting the fouling organism attachment and colonization processes, especially organic matter generated from marine culture activities.